PENGARUH LINGKUNGAN KERJA, KOMUNIKASI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PT. SAMACO - Bayu Rama Laksono; Acynthia Ayu Wilasittha (BAJ: Behavioral Accounting Journal, 2021)
Employee performance occurs due to work and communication environment factors. A comfortable and conducive work environment that supports employees will improve employee performance. Good communication and continuously maintained among fellow colleagues will make them compact and always work together in completing tasks given by the company. Then motivation is also a form of employee encouragement to always be enthusiastic in improving employee performance. A total of 300 employees of PT. Samaco is made into a population and taken as many as 75 respondents. Questionnaires were distributed to respondents, then the results will be analyzed by analyzing multiple linear regression, the t-test and F-test hypotheses. This study found that work environment, communication and motivation variables had a partial and synchronous effect on the work execution variables of PT. Samaco.